Penggunaan Metode Gallery Walk dalam Meningkatkan Pemahaman Belajar Peserta Didik - Sri Muawiah; Abd. Rahman K.; Zulfiqar Busrah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2021)
Education often experiences several obstacles, especially at the primary school level experiencing difficulties related to the learning process. The use of the gallery walk method in increasing the understanding and learning development of students is considered significant to be applied. This research is a type of field research which uses the type of Penelitian Tindakan Kelas (PTK) which consists of 2 cycles (I and II) through data analysis, namely data reduction, data exposure and data inference. The implementation of cycle I shows the acquisition of understanding of Islamic religious education of students (67.62), and there are about 4 students who gain comprehension of learning outcomes in the good category (76.7%), meanwhile cycle II shows an average score of learning comprehension of students (80.62), and there are about 7 students who obtain comprehension of learning outcomes in the excellent category (73.3%). Thus, students as a whole can understand the subject matter with the application of the gallery walk method.